The Pennsylvania Rural Health Model: Hospitals' Early Experiences With Global Payment for Rural Communities. Issue 3 (8th May 2022) - Scanlon, Dennis; Sciegaj, Mark; Wolf, Laura J.; Vanderbrink, Jocelyn; Johannes, Bobbie; Shaw, Bethany; Shumaker, Kassidy; Farley, Diane; Kitt-Lewis, Erin; Davis, Lisa
SUMMARY: Goal: In January 2019, the first cohort of rural hospitals began to operate under the Pennsylvania Rural Health Model for all-payer prospective global budget reimbursement as part of a demonstration funded by the Center for Medicare and Medicaid Innovation. Using information from primary source documents and interviews with key stakeholders, we sought to identify challenges and lessons learned throughout the design, development, and early implementation stages of the model. Methods: We relied on two qualitative research approaches: (1) review of primary source documents such as peer-reviewed publications and news accounts related to the model and (2) semistructured interviews with key staff and stakeholders, including current and former members of the Pennsylvania Department of Health, first-year applicant hospitals, technical assistance providers, and members of state and federal organizations and agencies familiar with the Pennsylvania and Maryland payment reform efforts for rural health and rural hospitals ( N = 20). Principal Findings: We identified four primary attributes that innovative projects such as the model need: (1) a champion at the state and hospital level, significant cooperation across state agencies and between federal and state agencies, and support from nongovernment stakeholders; (2) ongoing engagement and education of all stakeholders, particularly related to rural health disparities, the challenges faced by rural hospitals (especially resource limitations), and the differences between rural and urban health and health service delivery; (3) realistic time lines, noting that stakeholder relationships with hospital leadership develop over many months; and (4) multistakeholder collaboration, because participating hospitals must have ongoing engagement with community members (i.e., consumers of healthcare), nonacute community partners, and other rural hospitals to foster a "rural health movement." Applications to Practice: A successful Pennsylvania model holds promise for other states seeking to address the needs of rural populations and the hospitals that are vital to those communities. The lessons in this article can assist others in making the transition from volume to value in rural healthcare.